9514 1404 393
Answer:
(a) no
(b) no
Step-by-step explanation:
The two questions are asking essentially the same thing. There is nothing that indicates DC ≅ DB or that AC ≅ AB. One (both) of these conditions is (are) required for ΔBAC to be isosceles, so that AD is both a perpendicular bisector of BC and a bisector of angle BAC.
There is not enough information to answer either question affirmatively.
I’m confused, can you explain
Answer:
Step-by-step explanation:
abc = 1
We have to prove that,
![\frac{1}{1+a+b^{-1}}+\frac{1}{1+b+c^{-1}}+\frac{1}{1+c+a^{-1}}=1](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B1%2Ba%2Bb%5E%7B-1%7D%7D%2B%5Cfrac%7B1%7D%7B1%2Bb%2Bc%5E%7B-1%7D%7D%2B%5Cfrac%7B1%7D%7B1%2Bc%2Ba%5E%7B-1%7D%7D%3D1)
We take left hand side of the given equation and solve it,
![\frac{1}{1+a+\frac{1}{b}}+\frac{1}{1+b+\frac{1}{c}}+\frac{1}{1+c+\frac{1}{a}}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B1%2Ba%2B%5Cfrac%7B1%7D%7Bb%7D%7D%2B%5Cfrac%7B1%7D%7B1%2Bb%2B%5Cfrac%7B1%7D%7Bc%7D%7D%2B%5Cfrac%7B1%7D%7B1%2Bc%2B%5Cfrac%7B1%7D%7Ba%7D%7D)
Since, abc = 1,
and c = ![\frac{1}{ab}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bab%7D)
By substituting these values in the expression,
![\frac{1}{1+a+\frac{1}{b}}+\frac{1}{1+b+\frac{1}{c}}+\frac{1}{1+c+\frac{1}{a}}=\frac{1}{1+a+\frac{1}{b}}+\frac{1}{1+b+ab}+\frac{1}{1+\frac{1}{ab}+\frac{1}{a}}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B1%2Ba%2B%5Cfrac%7B1%7D%7Bb%7D%7D%2B%5Cfrac%7B1%7D%7B1%2Bb%2B%5Cfrac%7B1%7D%7Bc%7D%7D%2B%5Cfrac%7B1%7D%7B1%2Bc%2B%5Cfrac%7B1%7D%7Ba%7D%7D%3D%5Cfrac%7B1%7D%7B1%2Ba%2B%5Cfrac%7B1%7D%7Bb%7D%7D%2B%5Cfrac%7B1%7D%7B1%2Bb%2Bab%7D%2B%5Cfrac%7B1%7D%7B1%2B%5Cfrac%7B1%7D%7Bab%7D%2B%5Cfrac%7B1%7D%7Ba%7D%7D)
![=\frac{b}{b+ab+1}+\frac{1}{1+b+ab}+\frac{ab}{ab+1+b}](https://tex.z-dn.net/?f=%3D%5Cfrac%7Bb%7D%7Bb%2Bab%2B1%7D%2B%5Cfrac%7B1%7D%7B1%2Bb%2Bab%7D%2B%5Cfrac%7Bab%7D%7Bab%2B1%2Bb%7D)
![=\frac{1+b+ab}{1+b+ab}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B1%2Bb%2Bab%7D%7B1%2Bb%2Bab%7D)
![=1](https://tex.z-dn.net/?f=%3D1)
Which equal to the right hand side of the equation.
Hence, ![\frac{1}{1+a+b^{-1}}+\frac{1}{1+b+c^{-1}}+\frac{1}{1+c+a^{-1}}=1](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B1%2Ba%2Bb%5E%7B-1%7D%7D%2B%5Cfrac%7B1%7D%7B1%2Bb%2Bc%5E%7B-1%7D%7D%2B%5Cfrac%7B1%7D%7B1%2Bc%2Ba%5E%7B-1%7D%7D%3D1)
Ans: About 2.30
-15 x 3.16 / 9 = x sqrt
-15 x 3.16 = - 47.4
-47.4 / 9 = -5.27
-5.27 sqrt = About 2.30
Hope this helped :)
Answer:
the answer is A
Step-by-step explanation:
-17 - (-7) = -24
a = -24